Peran dan Tanggung Jawab Platform Digital dalam Upaya Pengenaan Pajak di Indonesia Era Society 5.0 Menurut Undang-Undang Harmonisasi Peraturan Perpajakan dan Undang-Undang Informasi dan Transaksi Elektronik - Revina Putri Utami; Amelia Cahyadini; Tasya Safiranita (Pusat Riset dan Inovasi Nasional, 2025)
Technological advancements in the Society 5.0 era have transformed the economic landscape, including taxation mechanisms. This study focuses on the role and responsibilities of digital platforms in tax imposition in Indonesia, governed by various regulations such as the Harmonized Tax Law (UU HPP) and Electronic Information and Transaction Law (UU ITE). The study finds that while digital platforms are central to the digital economy, existing regulations have not fully addressed the complexity of their operations, particularly in the context of taxation. Using a normative juridical approach, this research examines key challenges such as transaction anonymity, taxation disparities between conventional and digital companies, and tax avoidance by multinational digital platforms. On the other hand, the Indonesian government has initiated adaptation efforts by imposing Value-Added Tax (VAT) on digital trade, although its implementation still faces technical and administrative barriers. The study concludes that Indonesia's tax regulations need reforms to better accommodate the dynamics of the digital economy, including implementing fair and legally certain taxes for digital platforms. Recommendations include strengthening oversight, enhancing international collaboration, and utilizing technology to improve transparency and efficiency in the tax system. This research aims to contribute to the government, regulators, and business actors in creating an inclusive and sustainable digital economic ecosystem.